The impact of profitability on stock prices: The moderating role of firm size in publicly listed companies - Aswin Sauwamah; Vivin Gotama Tie; Imang Dapit Pamungkas (Proceeding International Conference on Accounting and Finance, 2025)
This research aims to analyze the effect of profitability on stock prices with firm size as a moderating variable. The population in this study consists of manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange. The sample companies during the years 2021-2023 are 78 companies that meet the criteria determined through purposive sampling method. The research data was analyzed using moderation regression analysis based on data processing results with SPSS Version 25. The research results show that profitability affects stock prices and firm size does not moderate the effect of profitability on stock prices.